Inhibition of Cellulase Activity Fusarium oxysporum f. sp. lycopersici Pathogens in Tomato Plants Using Essential Oils from Citronella in Vitro - Musafir, Musafir; Martosudiro, Mintarto; Muhibuddin, Anton (Universitas Panji Sakti, 2025)
The purpose of this study is to determine the ability of essential oils from citronella plants to inhibit cellulase enzyme activity in the fungus Fusarium oxysporum f. sp. lycopersici. and evaluate its potential as a disease-control material in tomato plants. This research was carried out in August 2023 until completed in February 2024. The method used in this study is experimental which consists of the process of exploring the fungus that causes disease in tomato plants, microscopic characterization of fungal isolates, molecular identification, inhibition test of fungal colony growth using essential oils from citronella plants, cellulase enzyme activity test, and cellulase enzyme activity inhibition test using essential oils from citronella plants. The variables observed in this study consisted of inhibiting the growth of Fusarium oxysporum f. sp. lycopersici. By essential oils, test the activity of quantitative cellulase enzymes, and cellulase enzymes activity inhibition test using essential oil from citronella plant. The results of microscopic characterization and molecular tests show that the fungal isolate used in this study has 99% similarity with Fusarium oxysporum f. sp. lycopersici. Essential oils extracted from citronella plants effectively inhibit the formation of fungal colonies. This is evidenced by the results of observation at the age of 7 HSI mushrooms with the growth diameter of fungal colonies of 5.06 cm, 3.56 cm, and 2.44 cm after applying essential oils with concentrations of 333 ppm, 666 ppm, and 1000 ppm. Results of observation and calculation of cellulase enzyme activity values in Fusarium oxysporum f. sp. lycopersici isolate. Cellulase enzyme activity of 0.831 U/mL was obtained. The application of essential oils with sequential concentrations (333 ppm, 666 ppm, and 1000 ppm) was able to decrease the activity of cellulase enzymes, with activity inhibition of 31%, 39%, and 44% in Fusarium oxysporum f. sp. lycopersici isolates.